Crystallization and preliminary crystallographic analysis of dextranase from Streptococcus mutans - Suzuki, Nobuhiro (International Union of Crystallography, 2011)

(untitled)
Streptococcus mutans dextranase hydrolyzes the internal α-1,6-linkages of dextran and belongs to glycoside hydrolase family 66. An N- and C-terminal deletion mutant of S. mutans dextranase was crystallized by the sitting-drop vapour-diffusion method. The crystals diffracted to a resolution of 1.6 Å and belonged to space group P2(1), with unit-cell parameters a = 53.2, b = 89.7, c = 63.3 Å, β = 102.3°. Assuming that the asymmetric unit of the crystal contained one molecule, the Matthews coefficient was calculated to be 4.07 Å(3) Da(−1); assuming the presence of two molecules in the asymmetric unit it was calculated to be 2.03 Å(3) Da(−1).